History, hagiography, romance… - Lisa M. Ruch (Medievalista)
Athelstan’s reputation and accomplishments as the king credited with being the first to rule over all of England led to his being celebrated in the Middle Ages in art, coinage, romance, travel narratives, and chronicles. In the prose Brut tradition, his depiction is, for the most part, focused on his military accomplishments, with little elaboration. However, the abbreviated Middle English prose Brut preserved in Edinburgh University Library MS 184 and two other manuscripts is unusual in its blending of narrative elements from historical accounts, hagiography, and romance to portray Athelstan as an English hero, and in its telling its 15-century audience where they could still see physical relics of Athelstan’s reign in their own day, giving them the opportunity to be vicariously connected to the storied history of their nation. This article traces sources and traditions this Brut’s compiler most likely drew from and considers what implications this may have for our understanding of this particular manuscript and of the evolution and adaptation of Brut chronicles in the late Middle Ages.